Innovations in green technology for increasing major grain crop production and efficiency in China - Fulin ZHAO; Xingbang WANG; Wushuai ZHANG; Peng HOU; Qingfeng MENG; Zhenling CUI; Xinping CHEN (Frontiers of Agricultural Science and Engineering)
The implementation of green technologies has facilitated the sustainable development of China’s agriculture. However, the impact of green technologies in China’s major crops production, their mechanisms of action and their future potential have not been systematically investigated. This study used national statistics data to summarize the impact of technological innovation on production and efficiency of major grain crops in China, and to identify which technologies have made the most important contributions. National statistics data showed changes in grain production (58% increase), total planting area (8.6% increase) and structure, nutrient input (0.83 Mt decrease) and reactive nitrogen losses, and optimized planting and fertilizer structure in 2022 compared to 2000. Of these, the proposal of integrated soil-crop system management significantly decreased reactive nitrogen losses and greenhouse gas emissions by 30% and 11%, respectively. Root zone nutrient regulation techniques, such as in-season nitrogen management, increased yields by 8% and decreased nitrogen rate by 25%. Rhizosphere nutrient regulation technology increased yield by 20.2% and decreased nitrogen rate by 20%–30%. According to predictions, integrated soil-crop system management will demonstrate significant advantages in both unit area yield and total yield by the year 2050. The adoption of integrated soil-crop system management is expected to increase the total production of rice, wheat and maize by 45.8, 115 and 360 Mt, respectively. Currently, China’s agriculture is confronted by significant challenges, including rising food demand, excessive inorganic nutrient inputs, and low utilization rates of organic resources. Three key recommendations arise from this study: the implementation of precise management for organic manure; the promotion of enhanced-efficiency fertilizers; and the adoption of new technologies including integrated soil-crop system management combined with rhizosphere nutrient regulation and intelligent nutrient management. These measures will drive the development of green, high-yield and efficient agriculture.